2015
DOI: 10.4209/aaqr.2015.07.0482
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Exhaust Emissions of a Diesel Generator Fueled with Water-Containing Butanol and Waste-Edible-Oil-Biodiesel Blends

Abstract: In recent years, the development of alternative energies has attracted much interest owing to the depletion of crude oil reserves and increasing oil prices. Many efforts have been made to use biodiesel as an alternative fuel in diesel engines. This study examines the particulate matter (PM), particulate carbon (EC and OC), and polycyclic aromatic hydrocarbons (PAHs) that are emitted from a generator using biodieselhols, which comprise 10-50 vol% pure (or dehydrated) butanol (denoted as B) or 10-40 vol% water-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…The premium diesel fuel was obtained from the Chinese Petroleum Corporation, Taiwan, and the pure WCO-biodiesel was manufactured by Chant Oil Co. Ltd., Taiwan. Further details of the fuel compositions and sampling programs can be found elsewhere (Tsai et al, 2015b(Tsai et al, , 2016.…”
Section: Sampling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The premium diesel fuel was obtained from the Chinese Petroleum Corporation, Taiwan, and the pure WCO-biodiesel was manufactured by Chant Oil Co. Ltd., Taiwan. Further details of the fuel compositions and sampling programs can be found elsewhere (Tsai et al, 2015b(Tsai et al, , 2016.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…The WCO-based biodiesel blends were also been reported as an greener fuel for POP reduction in both internal combustion engine and incinerators since they could enhance the oxidation of hydrocarbons and further inhibit the reformation of POPs from C 2 H 2 precursor (Tsai et al, 2015b(Tsai et al, , 2016Chen et al, 2017). Table 3 shows the emission factors (EFs) of BaP eq in term of unit fuel consumption and power generation by using D100, W20 and W40 at the two engine loads.…”
Section: Pah Emissions and Toxicities In The Exhaust Of Diesel Enginementioning
confidence: 99%
“…They are primarily derived from the incomplete combustion and pyrolysis of organic substances and are produced through both natural and anthropogenic sources. Forest fires and volcanic eruptions (Kim et al, 2003) produce natural PAHs, whereas the burning of coal, wood, incense, candles, cigarettes, mosquito coils, household fuel, gasoline, diesel, and the use of cooking and industrial processes produce anthropogenic PAHs (Mastral and Callen, 2000;Bzdusek et al, 2004;Orecchio, 2011;Yang et al, 2012;Cheruiyot et al, 2015;Tiwari et al, 2015;Tsai et al, 2015;Yang et al, 2015). The following chemicals have been recognized as confirmed (1), probable (2A) and possible (2B) carcinogens for humans (IARC, 2016): benzo[a]pyrene (BaP) (1), dibenz [a,h]anthracene (DBA) (2A), benzo [a]anthracene (BaA) (2B), chrysene (Chr) (2B), benzo [b]fluoranthene (BbF) (2B), benzo [k]fluoranthene (BkF) (2B), indeno [1,2,3-cd]pyrene (INP) (2B), and naphthalene (Nap) (2B).…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies indicated that the oxygenated additives in diesel can improve the thermal efficiency of engine and reduce the BSFC (Yoshimoto et al, 1999;Lin et al, 2006;Lin et al, 2010;Mwangi et al, 2015a;Tsai et al, 2015b). However, the alternative ratios in the current study were too high to overcome the loss of heating values.…”
Section: Fuelsmentioning
confidence: 46%